EARLY VENDIAN AGE OF MULTIPLE GABBRO-GRANITE COMPLEXES OF THE KARALON-MAMAKAN ZONE, BAIKAL-MUYA BELT: NEW U-PB ZIRCON DATA - Rytsk E.Yu.; Makeev A.F.; Glebovitsky V.A.; Fedoseenko A.M. (My University, 2007)
The Karalon–Mamakan zone is situated in the eastern margin of the Baikal–Muya belt and consists of the Mamakan and Karalon segments. Two multiple intrusive complexes, the Early Proterozoic Muya gabbrodiorite and Middle Proterozoic Vitim diorite–granite complexes, were distinguished by Salop in the Karalon segment (Middle Vitim mountainous region). During subsequent works, mutually intersecting diorite and granitoid intrusions on the left bank of the middle Vitim River (Padora–Orlov interfluve) were combined into the multiphase Padora complex, while leucoplagiogranites with an age of 537 ± 9 Ma were identified as the Maloyakornyi Complex. Recent geochronological data showed that plagiogranites of the Tallaya (Muya plagiogranites) gabbrodiorite–plagiogranite pluton in the Vitim–Tallaya–Padora interfluve have a U–Pb zircon age of 625 ± 14 Ma; gabbroids of the Zaoblachnyi pyroxenite–gabbronorite pluton define a Sm–Nd isochron age of 612 ± 34 Ma.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский